PENGARUH METODE SQ3R TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN PESERTA DIDIK KELAS IV SDN 2 RUMAK TAHUN PELAJARAN 2020/2021 - Dian Kirana Dewi; Safruddin Safruddin; Heri Setiawan; Muhammad Makki (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2021)
The purpose of this study is to find out if there is an influence of SQ3R method on the ability to read the understanding of grade IV students at SDN 2 Rumak. The type of research used is experimental research with Quasi Experimental Design form Nonequivalent Control Group Design. The population in this study was all students of grade IV SDN 2 Rumak, while the samples in this study were grade IV SDN 2 Rumak as control class and grade IV SDN 2 Rumak as experimental class. The sampling technique used is saturated sampling. The data collection techniques used are tests and documentation. The tests used in this study serve to measure the ability to read the understanding of students in a predetermined sample, while documentation is used to obtain data on the number of students and the list of names of grade IV students at SDN 2 Rumak. Data on the ability to read the understanding of learners in the form of pretest and posstest then in the analysis using normality test with kolmogrov smirnov test, then in homogeneity test with f variant. For the determination of hypothesis test can be done by comparing the value of thitung 4,787 with ttabel 2.018 where the value of thitung ≥ ttabel or by looking at the value of Sig. (2-tailed) 0.000 ≤ 0.05 at a rate of significance of 5% with df 42 then Ha accepted and H0 rejected. So it can be concluded that there is an influence of SQ3R learning methods on the Ability to Read Understanding of grade IV students at SDN 2 Rumak in the 2020/2021 school year.